Shaping Global Health Policy - Kaasch, Alexandra. author. aut Link
XI, 172 p.
Keywords: Using an approach that combines transnational and comparative social policy analysis with international relations, this book assesses various global social policy actors and compares their ideas and prescriptions about national health care systems. It highlights the importance of considering health policies across multiple scales.